What Drives Inventory Accumulation? News on Rates of Return and Marginal Costs - Christoph Görtz; Christopher Gunn; Thomas A. Lubik (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the effects of news shocks on inventory accumulation in a structural VAR framework. We establish that inventories react strongly and positively to news about future increases in total factor productivity. Theory suggests that the transmission channel of news shocks to inventories works through movements in marginal costs, through movements in sales, or through interest rates. We provide evidence that changes in external and internal rates of return are central to the transmission for such news shocks. We do not find evidence of a strong substitution effect that shifts production from the present into the future.
Keywords: C32; E22; E32; G31; 330; structural VAR; news shocks; inventories